IST2: an insertion sequence from Thiobacillus ferrooxidans. - Yates, J R (1988)
The genome of Thiobacillus ferrooxidans (strain ATCC 19859) contains at least two families of repeated sequences, termed family 1 and 2. The nucleotide sequence of a family 2 member was determined. It is 1408 base pairs long and has structural features similar to those of insertion sequences (IS elements). Terminal inverted repeats 25 base pairs in length are present. These inverted repeats are imperfect and adjacent to target-site duplications 9 base pairs in length. Several open reading frames were detected (the longest was 888 base pairs). We have named this IS element-like sequence IST2. The ends of a second example of IST2 were analyzed and compared to those of the first. The DNA sequences are identical and similarly sized target-site duplications are present.